Risk Stratification for the Rate and Location of Residual Bladder Tumor for the Decision of Re-Transurethral Resection of Bladder Tumor - Fan, Junjie; Zhang, Xing; Fan, Jinhai; Li, Lei; He, Dalin; Wu, Kaijie (Frontiers in Oncology, 2022)
Introduction To assess the rate and location of residual tumor in re-transurethral resection of bladder tumor (re-TURBT) and develop a risk stratification tool to assist clinicians in making treatment decisions. Patients and Methods The data of 144 patients with high-risk bladder cancer who received re-TURBT were retrospectively reviewed. The rate and location of residual tumors was recorded. Logistic regression was performed to explore risk factors for residual tumors, and a risk classification tool was developed. Results Among the 144 patients, the rates of residual tumor and tumor location at the base of the primary tumor were 22.2% and 10.4%, respectively. Non-urothelial carcinoma subspecialist, piecemeal resection and the absence of detrusor muscle in the first specimen were defined as risk factors. Patients were categorized into low-, intermediate-, and high-risk groups according to the number of risk factors. The rate of residual tumor in the high-risk group was significantly higher than that in the low- and intermediate-risk groups (50% vs. 7.8%, P=0.001; 50% vs. 18.6%, P=0.002). Moreover, high-risk patients benefitted more from a second resection at the base of the primary tumor due to the high rate of residual tumor located at this site than low- and intermediate-risk patients (23.5% vs. 2.0%, P=0.002; 23.5% vs. 10.2%, P=0.083). Conclusions Risk stratification based on the subspecialist category, operative method, and presence or absence of detrusor muscle in the first specimen could help identify patients who benefit from re-TURBT and second resection the base of the primary tumor.